Role of Mitochondrial Stress Protein HSP60 in Diabetes-Induced Neuroinflammation - Donisha Shani Niharika Keembiya Liyanagamage; Ryan D. Martinus (Mediators of Inflammation)
Diabetes mellitus is the most common metabolic disorder characterized by hyperglycemia and associated malfunctions of the metabolism of carbohydrates, proteins, and lipids. There is increasing evidence of a relationship between diabetes and vascular dementia. Interestingly, hyperglycemia-linked neuroinflammation in the central nervous system is considered to play a key role during vascular dementia in diabetic patients. However, the mechanisms responsible for the relationship between hyperglycemia and neuroinflammation is not clearly understood. Diabetes-induced alternations in the blood-brain barrier permit high glucose influx into the brain cells via glucose transporters and promote oxidative stress through overproduction of reactive oxygen species. Despite many studies demonstrating a link between oxidative stress and mitochondrial dysfunction, the relationship between mitochondrial dysfunction and neuron inflammation during hyperglycemia remains to be established. In this review, we will focus on diabetes-induced changes in the central nervous system and the role of mitochondrial heat shock protein 60 (HSP60) as an initiator of oxidative stress and potential modulator of neuroinflammation. We suggest that oxidative stress-mediated mitochondrial dysfunction stimulates the upregulation of mitochondrial heat shock protein 60 (HSP60) and ultimately initiates inflammatory pathways by activating pattern recognition receptors. HSP60 also could be a focal point in the development of a biomarker of neuroinflammation as HSP60 is known to be significantly elevated in diabetic patients. Interestingly, extracellular secretion of HSP60 via exosomes suggests that inflammation could spread to neighboring astrocytes by activating pattern recognition receptors of astrocytes via neuronal exosomes containing HSP60. A mechanism for linking neuron and astrocyte inflammation will provide new therapeutic approaches to modulate neuroinflammation and therefore potentially ameliorate the cognitive impairment in diabetic brains associated with vascular dementia.